UNLAWFUL ACTS AND LAND DISPUTES: UNDERSTANDING OWNERSHIP RIGHTS IN INDONESIA - Haidir, Rizki; Zaini, Zulfi Diane (Universitas Islam Negeri Alauddin Makassar, 2024)
Indonesia, an archipelagic nation with a tropical climate, fertile soil, and abundant natural resources, primarily supports its population through agriculture. Most people make their living as farmers, heavily reliant on the land. Because of its importance, there is a constant effort to own and control land. Land represents the earth's surface and is often defined by property boundaries. Its significance necessitates state regulations for land rights control. This study uses a normative and empirical juridical approach, collecting data through library research, observations, and interviews, followed by qualitative analysis. The findings reveal that land grabbing occurs mainly due to the absence of a Certificate of Ownership (SHM), with transactions based solely on a sale and purchase certificate lacking a receipt. Factors contributing to land grabbing include landowners' lack of awareness about their assets, victims' unawareness of land ownership, family members selling or giving away land without the victims' knowledge, and rising land prices driving people to seek land for farming. In case number 1/Pdt.G/2023/PN Mgl, the judge accepted the Plaintiff's lawsuit against the Defendant for unlawful acts. The trial demonstrated that the Defendant could not prove his claim of purchasing land from Helmi Majid. The Defendant failed to provide documentary evidence, and witness statements did not support his argument. After careful examination of the actions, events, evidence, and legal facts, the Panel of Judges found the Defendant had clearly violated Article 1365 of the Civil Code regarding Unlawful Acts. Consequently, the Panel of Judges rejected all of the Defendant's objections and granted part of the Plaintiff's claim.